Snakes and Ladders Media in Social Studies learning for Elementary School Students: Media Ular Tangga Pada pembelajaran IPS Siswa Sekolah Dasar - Septiyanto, Nurul Huda; N., Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2021)
This studi aims to analyze how the application of snake and ladder leraning media in social studies learning of elementary school students. This research uses a qualitative approach. The type of research used is a literature review. The data source in this research is secondary data theory obtained from the results of research that has been conducted by previous researchers. Methods of data collection using documentation. The data analysis technique in this study used descriptive analysis. The results of this study indicate that the application of snake and ladder learning media can increase students’ interest and social studies learning outcomes.